PENGEMBANGAN BAHAN AJAR BERBASIS KONTEKS SOSIOKULTURAL KOTA CIREBON DALAM PEMAHAMAN MATEMATIKA SISWA - Dede Malikhatul Ilmiah; Widodo Winarso (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
This study aims to produce educational materials based on the socio-cultural context of the city of Cirebon, which has a good and decent quality. The teaching materials can be used in the mathematical understanding of the students in MTs Riyadlul Ulum Bendungan. The type of learning material that is developed is a printed math module printed for class 7. The research method used is Research and Development which refers to the ADDIE development model. Where the development phases are: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The data collection techniques used in the research include; Sheets, questionnaires and Judge Expert tests. While qualitative and quantitative analyzes are used for data analysis. From the research results, the development of educational materials based on the socio-cultural context of the city of Cirebon in the understanding of mathematics students including a good category to be used in the process of learning mathematics. This, in line with the results of the students' answers to the teaching material, has developed quite well. In the results of limited tests and in-depth tests, the cutting of teaching materials takes up three aspects of evaluation (assessment of appearance, presentation of material and benefits). Thus also the results of the validation of the team of materials and media experts, that the developed teaching materials include categories worthy of being used in learning activities. then the teaching material, as a complement to teachers in teaching and can help students understand mathematics by promoting the local Cirebon of the wisdom of the city